Health assessment of harbour porpoises (PHOCOENA PHOCOENA) from Baltic area of Denmark, Germany, Poland and Latvia. (October 2020) - Siebert, U.; Pawliczka, I.; Benke, H.; von Vietinghoff, V.; Wolf, P.; Pilāts, V.; Kesselring, T.; Lehnert, K.; Prenger-Berninghoff, E.; Galatius, A.; Anker Kyhn, L.; Teilmann, J.; et al.
Highlights: Largest health assessment of harbour porpoises from the Baltic: from Latvia, Poland, Germany and Denmark. The animals were collected between 1990 and 2015 and were either by-caught or found dead on the coastline. The respiratory tract had the highest number of pathological lesions. 45.5 to 100% of the animals from the different countries were known by-caught individuals. Data on health status and the causes of death are valuable for management. Abstract: Harbour porpoise ( Phocoena phocoena ), the only resident cetacean species of the Baltic Sea is formed of two subpopulations populations, occurring in the western Baltic, Belt Seas and Kattegat and the Baltic Proper, respectively. Harbour porpoises throughout these areas are exposed to a large number of human activities causing direct and indirect effects on individuals, that might also harm this species on a population level. From Latvia, Poland, Germany and Denmark 385 out of 1769 collected dead harbour porpoises were suitable for extensive necropsy. The animals were collected between 1990 and 2015 and were either by-caught or found dead on the coastline. Following necropsies, histopathological, microbiological, virological and parasitological investigations were conducted. Females and males were equally distributed among the 385 animals. Most animals from the different countries were juveniles between 3 months and 3 years old (varying between 46.5 and 100% of 385 animals per country). The respiratory tract had the highest number of morphological lesions, including lungworms in 25 to 58% and pneumonia in 21 to 58% of the investigated animals. Of those with pneumonia 8 to 33% were moderate or severe. The alimentary, hearing, and haematopoietic systems had inflammatory lesions and parasitic infections with limited health impact. 45.5 to 100% of the animals from the different countries were known by-caught individuals, of which 20 to 100% varying between countries had netmarks. Inflammatory lesions, especially in the respiratory tract were found in higher numbers when compared to control populations in areas with less human activities such as arctic waters. The high number of morphological changes in the respiratory tract and of bycatches especially among immature animals before reaching sexual maturity is of serious concern, as well as the low number of adult animals among the material. Data on health status and the causes of death are valuable for management. A next step in this regard will combine data from health and genetic investigations in order to detect differences between the two populations of the Baltic.